Domestic and external monetary policy shocks and economic inequality in the Republic of Korea - Joon-ho Hahm; Dong Jin Lee; Cyn-Young Park (Asian Development Bank (ADB), 2022)
This paper investigates the effects of monetary policy shocks on income and wealth inequalities in the Republic of Korea. Using the detailed Household Income and Expenditure Survey and Korean Labor and Income Panel Study data, we construct measures of income and wealth inequality for the Korean economy. Empirical results show that both domestic and external monetary policy shocks exert significant countercyclical effects on income inequality. For wealth inequality, however, the effects are very different. Whereas domestic monetary policy shocks are insignificant, external policy shocks proxied by fluctuations in net capital flows seem to have significant effects on net wealth inequality.
Keywords: E52; D31; G51; E44; F42; 330; monetary policy; income inequality; wealth inequality; external monetary policy shock; emerging market economies